History, gendered space and organizational identity: An archival study of a university building. (May 2018) - Liu, Yihan; Grey, Christopher
How do buildings contribute to an organization's sense of what it is? In this article, we present the findings of a major archival study of an iconic university building to answer this question. Founded in the 19th century as a college for women, the building is analysed as a gendered space that embodies meanings that are selectively deployed and adapted by the present-day, now co-educational, university. By bringing together concepts of space and history so as to examine 'space in history' we show how over long periods of time what buildings 'say' about an organization change so that the past is both a legacy and a resource for shifting organizational identity.